Proceedings of the Fifth International Conference on Learning Analytics and Knowledge 2015
DOI: 10.1145/2723576.2723611
|View full text |Cite
|
Sign up to set email alerts
|

Identifying learning strategies associated with active use of video annotation software

Abstract: The higher education sector has seen a shift in teaching approaches over the past decade with an increase in the use of video for delivering lecture content as part of a flipped classroom or blended learning model. Advances in video technologies have provided opportunities for students to now annotate videos as a strategy to support their achievement of the intended learning outcomes. However, there are few studies exploring the relationship between video annotations, student approaches to learning, and academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 22 publications
1
26
0
1
Order By: Relevance
“…However, the data used for the study was largely based on self-reported information collected via pre and post surveys and interviews, albeit also included direct observations of student and teacher interactions with MAT. Recent studies (Gašević, Mirriahi, & Dawson, 2014;Pardo et al, 2015) have used video analytics techniques to analyse detailed event streams and investigate how first-year university students use and engage with video annotation tools.…”
Section: Engagement With Course Videosmentioning
confidence: 99%
“…However, the data used for the study was largely based on self-reported information collected via pre and post surveys and interviews, albeit also included direct observations of student and teacher interactions with MAT. Recent studies (Gašević, Mirriahi, & Dawson, 2014;Pardo et al, 2015) have used video analytics techniques to analyse detailed event streams and investigate how first-year university students use and engage with video annotation tools.…”
Section: Engagement With Course Videosmentioning
confidence: 99%
“…Video-based learning [27] is used in a wide spectrum of instructional settings, ranging from flipped classrooms [15], online learning and MOOCS [10,23] to informal learning using YouTube. However, watching videos is inherently a passive form of learning; in order to learn effectively, students need to engage with video content [3][4][5][6]13,20,27]. Engagement with videos can be facilitated by embedding interactive activities, such as quizzes and assessment problems [8,12,14,24], or by providing environments for collaborative annotation of videos [3].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from being one of the factors supported by the Five Senses Model, learning engagement is also an important indicator of student success in general. As suggested in de Raadt et al (2005) and Pardo et al (2015), students engaged with the learning environment tend to have better performance in examinations.…”
Section: Revised Study Process Questionnairementioning
confidence: 67%